2018
DOI: 10.3389/fmicb.2018.00371
|View full text |Cite
|
Sign up to set email alerts
|

Intrahost Norovirus Evolution in Chronic Infection Over 5 Years of Shedding in a Kidney Transplant Recipient

Abstract: Noroviruses are the leading cause of acute gastroenteritis, and they can affect humans of all age groups. In immunocompromised patients, norovirus infections can develop into chronic diarrhea or show prolonged asymptomatic virus shedding. Chronic norovirus infections are frequently reported for solid organ transplant recipients, with rapid intrahost norovirus evolution seen. In this report, we describe a case of chronic norovirus infection in an immunocompromised patient who was followed up for over 5 years. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…The obesogenic environment generates high levels of reactive oxygen species (ROS), which may contribute to the distinct evolutionary pressures in the obese state (48,49). Obesity has been proposed to trigger premature aging of the immune system (45,50,51), mirroring an immunocompromised state, and both aged (30) and immunocompromised (52,53) hosts promote the emergence of novel viral variants. With blunted immune responses (7,54) and extended viral shedding (20,22) in obese humans, the same phenomenon may occur with IAV.…”
Section: Discussionmentioning
confidence: 99%
“…The obesogenic environment generates high levels of reactive oxygen species (ROS), which may contribute to the distinct evolutionary pressures in the obese state (48,49). Obesity has been proposed to trigger premature aging of the immune system (45,50,51), mirroring an immunocompromised state, and both aged (30) and immunocompromised (52,53) hosts promote the emergence of novel viral variants. With blunted immune responses (7,54) and extended viral shedding (20,22) in obese humans, the same phenomenon may occur with IAV.…”
Section: Discussionmentioning
confidence: 99%
“…However, prolonged or even chronic norovirus infection can occur in individuals with primary or secondary immunodeficiency [78]. Chronic norovirus infection has been reported in several studies, most of which were associated with solid organ transplants [79,80,81], but also allogenic stem cell transplants [82,83], and patients with common variable immunodeficiency (CVID) [78]. The symptoms vary, from prolonged diarrhea to asymptomatic with recurrent diarrhea, with or without vomiting [79,84].…”
Section: Genetics Vs Immunity—prolonged Norovirus Infection In Imentioning
confidence: 99%
“…However, few studies have focused on the association of HBGA phenotypes or genotypes with chronic norovirus infection, and those that have were mainly conducted in a single individual. Individual studies of chronic GII.4 infection in a kidney transplant recipient [80] and a GII.3 infection in a heart transplant recipient [14] showed that the patients were secretors.…”
Section: Genetics Vs Immunity—prolonged Norovirus Infection In Imentioning
confidence: 99%
“…No bacterial, mycotic, or C. difficile toxin was detected, and no other common diarrhea-related virus was found in the stool. Although the blood was negative for NV (data not shown), the quantitative results showed that the concentration of NV in feces was stable at 10 6 copies/mL 10% (w/v) stool suspension, which was lower than that in acute infection and comparable to that in chronic infections (Ludwig et al, 2008;Steyer et al, 2018). We cannot determine whether the patient's fever and diarrhea were caused by NV.…”
Section: Discussionmentioning
confidence: 86%
“…It was found that numerous mutations in the capsid did not alter the HBGA binding profiles, and chronically infected patients might not generate novel variants that cause outbreaks (Doerflinger et al, 2017). However, there was more evidence that intrahost GII.4 evolution can lead to antigenic epitopes change, which may produce potential successive outbreak strains (Debbink et al, 2014;Mai et al, 2016;Steyer et al, 2018). Our data provided insight into the extensive genetic diversity and evolution of NVs in a patient following allo-HSCT, and suggested that novel variants of NV GII.4 with HBGA and antigenic site changes were produced; chronically infected cases may serve as a potential reservoir for novel NVs.…”
Section: Discussionmentioning
confidence: 99%